Associations between behavioural risk factors and overweight and obesity among adults in population-based samples from 31 countries - Pengpid, Supa; Peltzer, Karl (Obesity Research and Clinical Practice, 2017)
Concern about overweight and obesity is growing worldwide, and more research to examine behaviours associated with the risk for increased weight in adult populations is needed. The aim of this study was to estimate associations between behavioural risk factors and overweight and obesity among adults in nationally representative population samples from 20 countries in Europe, 8 countries in Asia, Australia, Chile and USA.
Obesity Research and Clinical Practice (2017)11,158-166
Keywords: Overweight; Smoking; Alcohol use; Fruits and Vegetable; Consumption; Physical activity; Obesity; Population